Prognostic value of serum CRP, IgM and IgA levels in children with Mycoplasma pneumoniae and pleural effusion : serum CRP, IgM and IgA levels in children with Mycoplasma pneumoniae - Guo, Huiqing (Journal of Medical Biochemistry, 2025)
Objective: To analyze the clinical characteristics, predictive factors and curative effects of mycoplasma pneumoniae (MP) infection combined with pleural effusion in children. Methods: The medical records of 200 children diagnosed with MP pneumonia in our hospital from January 2021 to December 2023 were retrospectively analyzed. According to the presence or absence of pleural effusion, all the children were divided into mycoplasma pneumoniae pneumonia (MPP) with pleural effusion group (100 cases) and MPP without pleural effusion group (100 cases). The differences in clinical manifestations, laboratory indicators, imaging examination, treatment plan and treatment effect between the two groups were compared. Multivariate Logistic regression model was used to analyze the potential predictors of MPP combined with pleural effusion. Result: Age, length of hospital stay CRP level, white blood cell count, neutrophil count, IgM level, left lung disease, intravenous glucocorticoid use, duration of fever during hospitalization and duration of antibiotic use in MPP group were higher than those in group without pleural effusion (P<0.05). The number of cases, bilateral lung lesions and IgA levels in autumn were significantly lower than those in the group without pleural effusion (P<0.05). Multivariate Logistic regression analysis showed that age, CRP, white blood cell count, autumn infection, IgM and IgA levels were correlated with pleural effusion. Conclusions: The predictors of MP infection with pleural effusion in children include age, CRP, WBC, autumn infection, IgM and IgA. These factors may contribute to the early identification and treatment of children with MP pneumonia combined with pleural effusion.